Tegumentary and visceral leishmaniases in Brazil: emerging anthropozoonosis and possibilities for their control Leishmanioses tegumentar e visceral no Brasil: antropozoonoses emergentes e perspectivas de controle - Mauro Célio de A. Marzochi; Keyla Belízia F. Marzochi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
The existence of a number of different species of Leishmania, the persistent increase in the infection rate of diseases caused by this parasite (tegumentary and visceral forms), the different epidemiological situations found in regions of both recent and older colonization, and the trend towards urbanization have led to the adoption of different strategies to control leishmaniases in Brazil. The control measures involve studies related to the parasite, vectors, sources of infection (animal and human), clinical aspects, geographical distribution, historical and socioeconomic factors, integration of health services, and adequate technologies for diagnosis, treatment, and immunoprophylaxis. Finally, successful control requires work with human communities, involving education, provision of information, health promotion, and participation of these communities in the planning, development, and maintenance of control programs. A ocorrência de várias espécies de Leishmania, o contínuo aumento das afecções causadas por esses parasitas (formas tegumentares e visceral) e as diferentes situações epidemiológicas encontradas, tanto em regiões de colonização recente quanto de colonização antiga, com tendência a urbanização, vem requerendo a adoção de diferentes estratégias para o controle dessas endemias no Brasil. Essas medidas demandam estudos relacionados aos parasitas, insetos vetores, fontes de infecção, aspectos clínicos, distribuição geográfica, fatores históricos e sócio-econômicos, integração dos serviços de saúde, tecnologias apropriadas de diagnóstico, tratamento e imunoprofilaxia. Finalmente, para o sucesso do controle, são requeridos esforços junto as comunidades humanas, envolvendo educação, provisão de informação, promoção da saúde e participação dessas comunidades no planejamento, desenvolvimento e manutenção dos programas adotados.